Beyond Humboldt's problem: reflections on biolinguistics and its relation to generative grammar. (July 2015) - Boeckx, Cedric
Abstract: Numerous authors treat the term 'biolinguistics' as synonymous with the generative enterprise. Although undeniably Chomskyan in orientation, biolinguistics should not be equated with generative grammar, as the latter does not often seek to go beyond the level of cognition and establish linking hypotheses with the brain. This article attempts to clarify the nature of biolinguistics, highlighting departures from the research agenda routinely assumed by generative practitioners. Highlights: Reconsideration of the biolinguistic program. Ethology as a model for biolinguistics Biolinguistics vs. generative grammar. Chomsky linguistics. Brain-based linguistic enterprise.